Long-Term Changes of Inflammatory Biomarkers in Individuals on Suppressive Three-Drug or Two-Drug Antiretroviral Regimens - Serrano-Villar, Sergio; López-Huertas, María Rosa; Jiménez, Daniel; Galera, Carlos; Martínez-Sanz, Javier; Moreno, Elena; Muriel, Alfonso; Gutiérrez, Félix; Busca, Carmen; Portilla, Joaquín; Bisbal, Otilia; Iribarren, José Antonio; et al. (Frontiers in Immunology, 2022)
Background: Because inflammation is associated with mortality and has been linked to HIV transcription in lymphoid tissues during ART, it is necessary to address the long-term effects of switching 3-drug (3DR) to 2-drug regimens (2DR) on inflammation. Methods: Nested study in the Spanish AIDS Research Network. We selected PWH ART-naive initiating 3DR who achieved viral suppression in the first 48 weeks and either remained on 3DR or switched to 2DR (3TC+bPI; 3TC+DTG; DTG+RPV). We assessed the trajectories on inflammatory markers during ART using multivariate piecewise mixed models. Results: We analyzed 619 plasma samples from 148 patients (3DR, N=90; 2DR, N=58), the median follow-up was 4.6 (IQR 3.2-6.2) years. There were no significant differences in baseline characteristics between groups. After adjusting for potential confounders, patients with 3DR experienced a slow decline of IL6, hs-CRP, sCD14, sCD163, and D-dimer over time. In contrast, compared to 3DR, switching to 2DR was associated with increases in IL-6 (p=0.001), hs-CRP (p=0.003), and D-dimer (p=0.001) after year 3 from virologic suppression. 2DR was associated with a higher risk of hs-CRP quartile increase (aOR 3.3, 95%CI 1.1-10) and D-dimer quartile increase (aOR 3.7, 95%CI 1.1-13). The adjusted biomarker trajectories did not reveal a distinct pattern according to the type of 2DR used (bPI vs DTG). Conclusions: In this study in virally suppressed individuals, maintaining 3DR was associated with a more favorable long-term inflammatory profile than switching to 2DR. The potential clinical implications of these findings on the development of non-AIDS events deserve further investigation.